Progeny evaluation in uniform nurseries - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1981)
The Bean Team Nursery (VEF) is the 1st uniform and multidisciplinary evaluation for adaptation and disease and insect resistance and is composed of advanced, coded CIAT hybrid lines from various breeding projects, the germplasm bank, and national programs. Among the bush bean entries, 16 percent showed resistant reactions to rust (Uromyces phaseoli) and 20 percent were intermediate. Entries resistant and intermediate to anthracnose (Colletotrichum lindemuthianum) were 34 and 24 percent, resp. The frequency of lines combining important traits also increased in the 1980 VEF. For example, 103 entries combine resistance to BCMV and anthracnose with non-black grain color, factors necessary for acceptability in Africa. Preliminary yield trials (EP) consisted of 105 lines (91 bush and 14 climbing) selected from 594 evaluated in the 1979 VEF. All EP materials were resistant to the Florida and NY 15 strains of BCMV. Also, 68 materials, out of the 105 evaluated, possessed resistance to 3 or more diseases or insect pests. Tables are included with the results obtained in climbing bean and bush bean yield trials at CIAT-Palmira and CIAT-Popayan. (Extract)